Innovative Structural Evaluation of a Dual-Function Cane for Elderly Mobility: A Finite Element Analysis Approach Using SolidWorks - Rafana, Hadad; Amrullah, Apip; Ma'ruf, Ma'ruf; Mahmud, Rizal (Journal of Mechanical Engineering, Science, and Innovation, 2025)
The increasing proportion of elderly individuals globally underscores the need for safe and ergonomic mobility aids that support independent living and enhance quality of life. This study presents a structural analysis of a multifunctional walking cane prototype, NeoMossa, which integrates an umbrella mechanism, aimed at addressing both mobility and environmental protection needs for elderly users. The analysis employed the Finite Element Method (FEM) using SolidWorks simulation software to evaluate the mechanical performance of the cane under static loading conditions of 300 N, 500 N, and 700 N. Key parameters assessed included Von Mises stress, strain, displacement, and factor of safety. The results demonstrated that all measured values remained within acceptable limits, with the highest stress recorded at 75.98 MPa and a minimum safety factor of 1.72 under the maximum load. These findings confirm that the cane structure is capable of withstanding typical user loads without risk of mechanical failure. The study affirms the feasibility of integrating multifunctional features into assistive devices without compromising structural safety, contributing valuable insight to the design and development of innovative mobility aids for the elderly.